Understanding Language Death in Czech-Moravian Texas - Hannan, Kevin (Research in Language, 2007)
Based on several decades of personal interaction with Texas speakers of Czech, the author’s article attempts to correlate social change with some specific stages of language obsolescence and language death. Many instances of language change in that community, as well as cultural and social change, may be explained by the linguistic model known as the wave theory. One hundred and fifty years passed between the introduction of Czech and the death of that language in Texas. From the mid-nineteenth through the mid-twentieth century, the Czech-Moravians represented a closed community in which individuals defined their identity primarily by the Czech language, ethnicity, and culture. In the final five decades of the twentieth century, as the social template representing Texas speakers of Czech disintegrated, spoken Czech ceased to function as a living language, and much of the ancestral culture connected with the language was lost. Today some among the elderly, described as semi-speakers, terminal speakers, or ‘‘rememberers’’ of language, retain a limited knowledge, but the ancestral language now has only a symbolic function.